Second molar intrusion: Continuous arch or loop mechanics? - Martins, Renato Parsekian [UNESP]; Shintcovsk, Ricardo Lima [UNESP]; Shintcovsk, Luegya Knop; Viecilli, Rodrigo; Martins, Lidia Parsekian [UNESP] (Elsevier B.V., 2018)
Introduction: Our aim was to compare the load systems produced by rectangular loops and continuous arch mechanics on intrusion of a maxillary second molar. Methods: An orthodontic appliance was passively bonded from second molar to second molar on a patient's model fixed to an orthodontic force tester. The second molars were extruded by 3 mm, and 2 mechanics systems were compared: beta-titanium rectangular loops and super-elastic nickel-titanium continuous arch. Vertical (Fz) and mesial (Fy) forces, and tipping moments around the buccal axis (Mx) at the tubes were collected at every 0.5 mm of deactivation. Repeated measures analysis of variance was used to detect differences between mechanics. The net Mx was also estimated at the center of resistance of each molar.Results: Significant differences were found between the mechanics at the tubes, except for the Mx in the first molar, and more importantly, at the centers of resistance of the molars: Fz forces were greater in the continuous arch than in the rectangular loops, which, on the other hand, produced lower Fy forces than the continuous arch. In the second molar, net Mx was low initially and changed with deactivation. In the continuous arch, net Mx decreased from -3.6 N.mm of mesial crown tipping to clinically insignificant levels after 2 mm of deactivation. In the first molar, net Mx was lower on the rectangular loop than on the continuous arch during the first 2 mm of deactivation and became similar in the last millimeter of deactivation. Additionally, the net Mx decreased with deactivation with both mechanics. Conclusion: Both mechanics can intrude the second molars. Although the rectangular loop produced less tipping in large deflections, the continuous arch was a better approach when less intrusion was required.